Formal assignation of the kissing bug triatoma lecticularia (Hemiptera: Reduviidae: Triatominae) to the genus paratriatoma - de Paiva, Vinicius Fernandes; de Oliveira, Jader; Galvão, Cleber; Justi, Silvia Andrade; Landa, José Manuel Ayala; Rosa, João Aristeu da [UNESP] (My University, 2021)
The subfamily Triatominae (Hemiptera: Reduviidae) comprises hematophagous insects that are vectors of Chagas disease; including species assigned to the genera Triatoma and Paratriatoma. Initial examination of Triatoma lecticularia revealed the hirsuteness covering the entire body—a characteristic and striking feature of members of the genus Paratriatoma—and a systematic study revealed several other morphological characters that are in diagnostic alignment with Paratriatoma. Based on the examination of several specimens (including the lectotype), and with the additional support of molecular and cytogenetic data, we propose the formal transferal of Triatoma lecticularia (Stål, 1859) into the genus Paratriatoma with the resulting new combination: Paratriatoma lecticularia (Stål, 1859) comb. nov. (Hemiptera: Reduviidae: Triatominae).
Keywords: Heteroptera; North America; Taxonomy; Triatomini; Vectors